(3GdYdd aj SQ GdWHjYIs - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3bGd HdjfhS GdMcje agh cGed GdWHGY Sdje ef GdCYQGV jYfi GdfaS ef GdCeQGV s
(3BNQgG (B:s
(3JeJ GdebGdI GdChdi dHdjfhS ai GKHGJ GdJhMjO s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdChdis
(3GdebGdI GdChdi ai CKHGJ GdJhMjOs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs